Efficient regeneration of in vitro derived plants and genetic fidelity assessment of Phalaenopsis orchid - Sarmah, Dipika; Mohapatra, Priyadarshani P.; Seleiman, Mahmoud F.; Mandal, Tapas; Mandal, Nirmal; Pramanik, Kartik; Jena, Chinmaya; Sow, Sumit; Alhammad, Bushra Ahmed; Ali, Nawab; Ranjan, Shivani; Wasonga, Daniel O. (Frontiers in Sustainable Food Systems, 2024)
This study uses inflorescence stalk node as explants to establish an efficient and quick Phalaenopsis orchids cloning procedure for the most significant monopodial orchid in floriculture, without callus formation. The current study aimed to develop a rapid and easy regeneration process utilizing flower stalk nodes as explants, while also evaluating the clonal fidelity of the in vitro micropropagated plants through the analysis of RAPD markers. The tissue-cultured plantlets were grown on a solidified half-strength Murashig and Skoog (MS) base medium enriched with 15% coconut water (CW), 150 mg L−1 activated charcoal, and a mixture of 6-benzylaminopurine, BAP (cytokinins) and α-napthalene acetic acid, NAA and indole 3-butyric acid, IBA (auxins). After 14 weeks of growth, the early production of shoot bud was reported in ½ MS medium enriched with 2.5 mg L−1 BAP alone. Maximum shoot bud multiplication was observed in ½ MS fortified with BAP (2.5 mg L−1) + NAA (1.0 mg L−1), while the lowest was observed in 1.5 mg L−1 BAP + 0.5 mg L−1 IBA after 4 months of culturing. In this investigation, roots emerged simultaneously with shoot elongation from the axil, indicating the absence of a distinct rooting stage. The largest number of roots (3.25) was produced by BAP (2.5 mg L−1) + IBA (1.0 mg L−1) compared to NAA. Control, on the other hand, displayed no signs of root growth. Tissue cultured plantlets with well developed root systems while planted in a potting mixture of brick and charcoal (1: 1) resulted in a 70% survival rate during hardening. The clonal faithfulness of in vitro regenerated crop plantlets to the mother plant was demonstrated by the DNA extraction method with ten micropropagated plants’ young leaves as well as the mother plant using random amplification of a polymorphic DNA marker.